A pilot clinical trial with losartan in Myhre syndrome. Issue 3 (24th December 2020) - Cappuccio, Gerarda; Caiazza, Martina; Roca, Alessandro; Melis, Daniela; Iuliano, Antonella; Matyas, Gabor; Rubino, Marta; Limongelli, Giuseppe; Brunetti‐Pierri, Nicola
Abstract: Introduction: Myhre syndrome (MS) is an ultra‐rare disorder due to pathogenic variants in the SMAD4 gene that encodes a protein regulating the TGF‐β pathway and extra‐cellular matrix (ECM) homeostasis. Main clinical features of MS include thickening of skin and joint stiffness. Previous studies showed that losartan improved ECM deposition in MS fibroblasts. Materials and methods: Four molecularly confirmed MS subjects (mean age 23.8 ± 17 years) were evaluated for: (a) skin thickness by Rodnan score, (b) joint range of motion (ROM) by goniometry, and (c) speckle‐tracking echocardiogram. Following baseline evaluations, three MS individuals received losartan for 12 months and pre‐defined endpoints were monitored after 6 and 12 months of treatment. Results: At baseline, Rodnan scores were increased, joint ROM was reduced, and speckle‐tracking echocardiogram revealed reduced myocardial strain. In three MS subjects, improvements in skin thickness, joint ROM and to a lesser extent of myocardial strain, were observed after 6 and 12 months of losartan treatment. Conclusions: Although further long‐term controlled clinical trials with a larger number of affected individuals are needed, the present study suggests that losartan might improve skin, joint and heart abnormalities of MS.